The Relationships between Moral Foundations, Social Beliefs and Attitudes towards Economic Inequality among Russian Youth: A Case Study of Altai Krai - Oleg A. Sychev; Irina N. Protasova (Peoples' Friendship University of Russia (RUDN University), 2020)
This article presents the results of an empirical study on the relationships between moral foundations, social beliefs and attitudes towards economic inequality among young people. The topic of attitudes towards economic inequality has primarily been considered by sociologists and economists in the context of group differences, while its psychological factors and correlations have remained understudied. Different negative consequences of economic inequality can be mediated by such psychological mechanisms as subjective perception of existing inequality or personal attitudes towards it, which indicate the significance of this problem. In our study, we put forward a hypothesis that attitudes towards economic inequality among young people are related to moral foundations and social beliefs. To test this hypothesis, a study was conducted with a sample of 215 students (21% of the sample were male). The subjects completed The Scales of Dangerous World Beliefs and Jungle World Beliefs by J. Duckitt, The Moral Foundations Questionnaire by J. Graham and colleagues, and The Scale of Beliefs about Inequality by J. Kluegel and E. Smith. One of the objectives of this study was the development of a Russian version of the questionnaire by J. Kluegel and E. Smith, which full version is given in the appendix of the article. The correlations revealed that attitudes towards inequality are related to moral foundations (fairness, purity, and loyalty) and beliefs in a jungle world. Additionally, structural equation modeling has shown that approval of equality and inequality is most closely related to family welfare. Furthermore, this study found that the relationship between attitudes towards inequality and individualizing moral foundations is mediated by beliefs in a jungle world. Thus, sense of fairness and the value of caring for the weak and defenseless is opposed to beliefs in a jungle world and approval of inequality.